BeiDou Satellites Assistant Determination by Receiving Other GNSS Downlink Signals - Lei Chen; Ke Zhang; Xiangwei Zhu; Yangbo Huang; Gang Ou; Huicui Liu (International Journal of Antennas and Propagation)
GNSS’s orbit determinations always rely on ground station or intersatellite links (ISL). In the emergency of satellite-to-ground links and ISL break-off, BeiDou navigation satellite system (BDS) satellites cannot determine their orbits. In this paper, we propose to add a spaceborne annular beam antenna for receiving the global positioning system (GPS) and global navigation satellite system (GLONASS) signals; therefore, the BDS satellites may be capable of determining their orbits by GPS/GLONASS signals. Firstly, the spectrum selection, the power isolation, the range of Doppler frequency shift, and changing rate are taken into account for the feasibility. Specifically, the L2 band signals are chosen for receiving and processing in order to prevent the overlapping of the receiving and transmitting signals. Secondly, the minimum number of visible satellites (MNVS), carrier-to-noise ratio (C/N0), dilution of precision (GDOP), and geometric distance root-mean-square (gdrms) are evaluated for acquiring the effective receiving antennas’ coverage ranges. Finally, the scheme of deploying 3 receiving antennas is proved to be optimal by analysis and simulations over the middle earth orbit (MEO), geostationary earth orbit (GEO), and the inclined geosynchronous satellite orbit (IGSO). The antennas’ structures and patterns are designed to draw a conclusion that installing GPS and GLONASS receivers on BDS satellites for emergent orbits determination is cost-effective.